GEOSTATISTICAL TEST USING LEAST SQUARE ADJUSTMENT COMPUTATION TO OBTAIN THE REDUCTION PARAMETER FOR DSM TO DEM CONVERSION (Study of Case: Cilacap, Indonesia) - Atriyon Julzarika (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2010)
Abstract. ALOS satellite is one of the natural resources satellites that can be used for 3D model applications. The problems of 3D model generation based on satellite imagery are the model always in Digital Surface Model (DSM), not in Digital Elevation Model (DEM). The reference system of 3D model that are produced by ALOS satellite image is still as surface for z axis, whereas x axis and y axis has been closed to 2D reference system in some certain datum and system of map projection. Therefore, it needs a research to observe the accuracy and the precision of ALOS satellite data using a least square adjustment in parameter methods. The results of this research will be used as a reference for next research to find a way for changing DSM from ALOS satellite image to be DEM automatically.